Post−surge geometry and thermal structure of Hørbyebreen, central Spitsbergen - Małecki, Jakub; Faucherre, Samuel; Strzelecki, Mateusz (Polish Polar Research, 2013)
Hørbyebreen surged in the 19th or early 20th century, as suggested by geomorphological evidences and looped medial moraines. In this study, we investigate its wide-spread geometry changes and geodetic mass balance with 1960 contour lines, 1990 and 2009 digital elevation models, in order to define the present-day state of the glacier. We also study its thermal structure from ground-penetrating radar data. Little is known on the glacier behaviour in the first part of the 20th century, but from the surge maximum until 1960 it has been retreating and losing its area. In the period 1960-1990, fast frontal thinning (2-3 m a-1) and a slow mass build-up in the higher zones (~0.15 m a-1) have been noted, resulting in generally negative mass balance (-0.40 ± 0.07 m w. eq. a-1). In the last studied period 1990-2009, the glacier showed an acceleration of mass loss (-0.64 m ± 0.07 w. eq. a-1) and no build-up was observed anymore. We conclude that Hørbyebreen system under present climate will not surge anymore and relate this behaviour to a considerable increase in summer temperature in Svalbard after 1990. Radar soundings indicate that the studied glacial system is polythermal, with temperate ice below 100-130 m depth. It has therefore not (or not yet) switched to cold-bedded, as has been suggested in previous works for some small Svalbard surge-type glaciers in a negative mass balance mode. This work is a part of the Dickson Land Ice Masses Evolution project (dil*ice), funded by the Polish National Science Centre through grant no. N N 306 062940.